SME Inter-Clustering Linkage of East Java: Among Business Strategy and Cooperatives - Susanto, Deni Aditya (Journal of Developing Economies, 2021)
The Indonesian SME cluster has not fully implemented the cluster concept, causing the SME cluster to stagnate. The Meubel SME Cluster of Pasuruan City and Malang City are two prime clusters working to show their economic crisis performance several times. This study aims to examine the factors of inter-firm linkage and business strategy on business performance. Methodologically, this study uses several analytical methods, namely multiple linear regression, to measure the influence between inter-firm linkage and business strategy variables on business performance, SWOT matrix to map strategy, and descriptive analysis to present non-parametric findings. This study analyzed 60 samples of MSEs from a population of 350 business units. The results of the study mentioned that aspects of business strategy (finance, marketing, human resources, research, development, and operations) had a more significant effect on business performance (sales, profits, assets, labor, and productivity) than inter-firm linkage (backward, forward, and horizontal). Through SWOT matrix analysis, the inter-clustering linkage of Malang City and Pasuruan cluster SMEs is naturally created. Access to raw materials and labor in the city of Malang began to be complicated even though consumers' potential from large tourists and access to adequate technology. In contrast, Pasuruan City is lt to do marketing because of geographical conditions' weakness even though the raw material resources and labor are abundant. The specialization of production is created with Pasuruan City as the production base and Malang City as the Marketing Base. Keywords: Cooperatives, Business Strategy, Inter-Clustering LinkageJEL: Q13, L21, C38